Precision and accuracy of imageless navigation versus freehand implantation of total hip arthroplasty: A systematic review and meta‐analysis. Issue 4 (29th May 2017) - Snijders, Thom; van Gaalen, S.M.; de Gast, A.
Abstract: Background: Total hip arthroplasty (THA) is named the most successful surgical procedure of the twentieth century. To remain a success in the twenty‐first century THA should meet the higher demands of patients and society with regard to technical and functional outcome, costs and implant survival. To meet these demands optimal acetabular cup positioning is necessary. An imageless navigation system (NAV) might prevent malpositioning of the acetabular cup in THA. The aim of this study has been to compare the precision and accuracy of the anteversion and inclination of the acetabular cup position after NAV implantation and after freehand implantation of THA. Methods: A systematic review and meta‐analysis was conducted to assess the precision (variance) and accuracy (deviation from the target) from all available high‐quality randomised control trials to date. Results: Six out of seven studies concluded a statistically significant difference in precision in anteversion between the NAV group and the freehand group. Five out of seven studies concluded a statistically significant difference in precision in inclination. There is a significantly better accuracy for the NAV group than for the freehand group for anteversion ( p = 0.002) and for inclination ( p = 0.01). Conclusion: This study showed that NAV placement is more precise and has an improved accuracy for anteversion and inclination than freehand placement of the acetabular cup. However, there is a lack of evidence to support an improved functional outcome and a reduction of complications and revisions.